The Influence of Competence and Organizational Culture on the Performance of Indonesian Navy Ammunition Warehouse Personnel - Willis, Willis (Dinasti International Journal of Management Science, 2025)
This study examines how competency and organizational culture affect the performance of personnel managing the Indonesian Navy's ammunition warehouses. Using a literature-based approach, the research explores the relationship between individual competencies, organizational culture values, and performance outcomes. The findings indicate that strong technical and managerial competencies, supported by a positive organizational culture, significantly enhance operational efficiency and workplace safety in ammunition warehouse management. These insights provide strategic recommendations for military institutions to develop training programs focused on competency improvement and strengthening organizational culture to achieve sustainable performance optimization.